Get the job you want, even when no one's hiring : take charge of your career, find a job you love, and earn what you deserve! - Myers, Ford R., 1954- (John Wiley & Sons, 2009)
"In Get the Job You Want, Even When No One's Hiring, career expert Ford R. Myers maps the new world of job search and reveals essential strategies for your success. You'll learn how to seize opportunities that aren't posted yet ... how to make yourself an instant asset to potential employers ... how to clearly stand-out as the best candidate ... and how to leverage social media, blogs, and other Web tools"--Resource description page